Acidogenesis and Two‐Phase Codigestion of Fats, Oils, and Greases and Municipal Biosolids. (1st November 2016) - Varin, Ross; Novak, John; Bott, Charles
ABSTRACT: : Acidogenic codigestion of fats, oils, and greases (FOG) was studied using suspended growth sludge digesters operated as batch fed reactors that were fed twice daily. The digesters were maintained at a 2‐day retention time and at 37 °C to mimic the acid phase of an acid‐gas digestion system. As FOG loading rates increased, volatile fatty acid (VFA) production was found to increase, although the percentage of VFA production compared to theoretical values decreased exponentially to just 20% at the highest loading rates. FOG matter was found to have accumulated in the reactor vessel in semi‐solid balls that floated near the liquid surface. Two‐phase codigestion of FOG was studied at 37 °C using Continuously Stirred Tank Reactors (CSTRs) as acid phase digesters (APD) operated with 2‐day retention times, followed by gas phase digesters (GPD) with 15‐day retention times. The two‐phase systems were compared by FOG addition to the APD versus GPD. FOG addition to the APD resulted in 88% destruction of LCFAs, whereas FOG addition to the GPD resulted in 95% destruction of LCFAs. Accumulated LCFAs were found in the APD receiving FOG and were primarily composed palmitic acid (16:0), followed by oleic acid (18:1) and stearic acid (18:0).